Metabolic effects of induced alkalosis during progressive forearm exercise to fatigue - Raymer, Graydon H; Marsh, Greg D; Kowalchuk, John M; Thompson, R. Terry (Journal of applied physiology (1985), 2004)
1 Department of Medical Biophysics, The University of Western Ontario, London N6A 5C1; 2 Imaging Division, The Lawson Health Research Institute, and Department of Radiology, St. Joseph's Health Care, London N6A 4V2; 3 School of Kinesiology, The University of Western Ontario, London N6A 3K7; 4 Canadian Centre for Activity and Aging, London N6G 2M3; and 5 Department of Physiology and Pharmacology, The University of Western Ontario, London, Ontario, Canada N6A 5C1 Submitted 24 November 2003 ; accepted in final form 28 January 2004 Metabolic alkalosis induced by sodium bicarbonate (NaHCO 3 ) ingestion has been shown to enhance performance during brief high-intensity exercise. The mechanisms associated with this increase in performance may include increased muscle phosphocreatine (PCr) breakdown, muscle glycogen utilization, and plasma lactate (Lac - pl ) accumulation. Together, these changes would imply a shift toward a greater contribution of anaerobic energy production, but this statement has been subject to debate. In the present study, subjects ( n = 6) performed a progressive wrist flexion exercise to volitional fatigue (0.5 Hz, 1421 min) in a control condition (Con) and after an oral dose of NaHCO 3 (Alk: 0.3 g/kg; 1.5 h before testing) to evaluate muscle metabolism over a complete range of exercise intensities. Phosphorus-31 magnetic resonance spectroscopy was used to continuously monitor intracellular pH, [PCr], [P i ], and [ATP] (brackets denote concentration). Blood samples drawn from a deep arm vein were analyzed with a blood gas-electrolyte analyzer to measure plasma pH, P CO 2 , and [Lac - ] pl , and plasma was calculated from pH and P CO 2 . NaHCO 3 ingestion resulted in an increased ( P < 0.05) plasma pH and throughout rest and exercise. Time to fatigue and peak power output were increased ( P < 0.05) by 12% in Alk. During exercise, a delayed ( P < 0.05) onset of intracellular acidosis (1.17 ± 0.26 vs. 1.28 ± 0.22 W, Con vs. Alk) and a delayed ( P < 0.05) onset of rapid increases in the [P i ]-to-[PCr] ratio (1.21 ± 0.30 vs. 1.30 ± 0.30 W) were observed in Alk. No differences in total [H + ], [P i ], or [Lac - ] pl accumulation were detected. In conclusion, NaHCO 3 ingestion was shown to increase plasma pH at rest, which resulted in a delayed onset of intracellular acidification during incremental exercise. Conversely, NaHCO 3 was not associated with increased [Lac - ] pl accumulation or PCr breakdown. sodium bicarbonate; intracellular pH; lactate; phosphorus-31 magnetic resonance spectroscopy; skeletal muscle; ergogenic aid Address for reprint requests and other correspondence: G. H. Raymer, Rm. G450, The Lawson Health Research Institute, St. Joseph's Health Care Centre, 268 Grosvenor St., London, Ontario, Canada N6A 4V2 (E-mail: graymeratlri.sjhc.london.on.ca ).